Spatial Planning Policy Analysis and Participation Support Society Towards Environmental Sustainability - Ayu Larasati; I Wayan Diana Putra Adnyana (Jurnal Indonesia Sosial Sains, 2024)
The research is purpose to find out implementation spatial planning policies on Bekasi city for stainable environmental management? Analytical methods used are: 1) Geo-physics analysis of land suitability analysis, 2) physical analysis; 3) Analysis of environmental management, 4) Analysis of socio-economic conditions, and 5) Analysis of Geographic Information System (GIS). The results obtained that spatial planning and environmental carrying capacity can be concluded that to meet the needs of diverse development needs to develop a spatial pattern of land use, coordinate, procedures for water and other resources in a unified a dynamic environment. To meet the needs of diverse development needs to develop a spatial pattern coordinate system guana land, procedures for water and other resources in a unified order dynamic environment. For that layout needs to be managed by an integrated pattern through a regional approach with respect to site natural environment, socio-cultural environment, and the artificial environment in accordance with its development. Good city spatial structure with more increased public participation in city layout is expected to be better. The parties involved in these activities the city department of administration, the whole society. There is a direct influence on the city hall community participation in maintaining a healthy environment, so if you want to increase public participation in maintaining a healthy environment can be done by increasing the city spatial planning. Knowledge to community environmental management in maintaining a healthy environment, can be done by improving environmental management Knowledge community.